The Influence Of Instagram Social Media Communication On Purchase Intention Through Brand Equity In Seblak Preanger Jember - Elwitrisnasafitri, Virghina Dhia; Ariyanti, Maya (International Journal Labs, 2024)
This research objectives are to determine the influence of Instagram social media communication on purchase intention through brand equity in Seblak Preanger Jember. This research used the Explanatory Research type. The population in this research is the number of followers of Instagram Seblak Preanger. The exact population size in this study is not known. The sampling method in this research was carried out using the Purposive Sampling method. This research used 21 indicators using 10 times the number of parameters to anticipate if there is an incomplete or damaged questionnaire, so the sample size in this research is 21 x 10 = 210 respondents. The data analysis method used Structural Equation Modeling (SEM) with the SmaprtPLS application. The research results showed that Firm Created Communication influenced Brand Equity, User Generated Communication influenced Brand Equity, Firm Created Communication influenced Purchase Intention, User Generated Communication influenced Purchase Intention, Brand Equity influenced Purchase Intention, Brand Equity is proven to mediate the influenced of Firm Created Communication on Purchase Intention, Brand Equity is proven to mediate the influenced of User Generated Communication on Purchase Intention.